Analysis Basic Skills of Rebt-Based Counselors in Overcoming Problems in Non-Formal Education Students - Netrawati, Netrawati; Neviyarni, Neviyarni; Sukma, Dina; Sari, Mustika; Hakim, Firdha Ainil (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2025)
Professionalism is the standard of specific abilities and skills required to describe a person's qualifications in carrying out their profession. The professional competence of counselors in Non-Formal Education in providing guidance and counseling services in non-formal training institutions and study groups. The method used in this research is qualitative. The data collection method used is through a questionnaire instrument on REBT counseling proficiency for school counselors obtained via Google Form to measure the competencies possessed by Non-Formal Education State counselors related to knowledge, skills in conducting REBT counseling, and skills in creating REBT modules. The research results show that the mastery of REBT counseling by non-formal education counselors falls into the high category due to the training provided. However, it is hoped that there will be follow-up actions from this training or workshop because not 100% of non-formal education counselors possess adequate skills in conducting REBT counseling. Keywords: Profesionalism, competence of school counsellors, REBT counseling